Current Treatment Options in Acute Limb Ischemia - Fluck, Friederika; Augustin, Anne Marie; Bley, Thorsten; Kickuth, Ralph (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Acute limb ischemia represents a clinical emergency with eventual limb loss and life-threatening consequences. It is characterized by a sudden decrease in limb perfusion. Acute ischemia is defined as a duration of symptoms for less than 14 days. Aging of the population increases the prevalence of acute limb ischemia. The two principal etiologies are arterial embolism and in situ thrombosis of an atherosclerotic artery. Immediate diagnosis, accurate assessment and urgent intervention when needed are crucial to save the limb and to prevent a major amputation. Delay in diagnosis and therapy may lead to irreversible ischemic damage.Method To assess the current treatment options in acute limb ischemia, this review is based on a selective literature search in PubMed representing the current state of research.Results and Conclusion Patients with acute limb ischemia should receive immediate anticoagulation. Treatment depends on the classification based on the degree of ischemia and limb viability. Especially acute (< 14 days symptom duration) Rutherford Categories IIa and IIb with marginally and immediately threatened limbs require definitive therapeutic intervention and are salvageable, if promptly revascularized. The current literature suggests that open surgical revascularization is more time effective then catheter-directed thrombolysis. However, with the advent of thrombolytic delivery systems and mechanical thrombectomy devices, treatment time can be minimized and successful utilization in patients with Category IIb (Rutherford Classification for Acute Limb Ischemia) has been reported with promising limb-salvage and survival rates. Large randomized studies are still missing, and guidelines suggest choosing the method of revascularization depending on anatomic location, etiology, and local practice patterns, with the time to restore the blood flow being an important factor to consider.Key points: Citation Format
Keywords: ischemia/infarction; thrombolysis; embolism/thrombosis; extremities; interventional procedures; acute